A high-capacity high-entropy oxyfluoride material, and methods of making and using the same
Patent Information
- Application Number
- CN202510392597.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-03-31
AI Technical Summary
目的是解决含钴材料容量不足、结构不稳定以及储能密度低等问题
[0031](1) This invention uses nickel source, M source, iron source, manganese source and magnesium source as raw materials, and combines them with fluorine substitutes. Through chemical and physical mixing and high-temperature pyrolysis, different kinds of metal oxide salts and fluorine substitutes are used to prepare layered fluorine oxides with small particle size, stable structure and high capacity and high entropy.
Smart Images

Figure CN120328640B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of structural energy storage composite materials, specifically to a high-capacity, high-entropy fluorine oxide material, its preparation method, and its applications. Background Technology
[0002] Electrification of transportation is one of the key technologies for reducing carbon dioxide emissions. Currently, lithium-ion batteries (LIBs) are widely used in energy storage devices in daily life due to their excellent energy storage performance, especially in the increasingly popular new energy electric vehicles and electric aircraft in recent years. However, the energy density of the most advanced LIBs is still unsatisfactory, which greatly hinders the range of electric transportation. To solve this problem, researchers have developed structural energy storage composite material devices (SESCDs), which combine energy storage and load-bearing functions. Therefore, a good structural energy storage composite material device must have two functions at the same time: (1) excellent energy storage performance; (2) the ability to serve as a load-bearing component. That is to say, SESCDs can serve as structural components that bear mechanical loads while also providing sufficient energy storage capacity; therefore, they are attractive not only for electric vehicles but also for many structural and energy needs in building materials and other fields in the future.
[0003] Currently, the limited theoretical capacity and energy density of commonly used commercial electrode materials greatly hinder the development of structural energy storage composite materials. Furthermore, the high specific capacity and energy density of lithium cobalt oxide and ternary materials are severely restricted in their application, production, and development due to resource scarcity and high cost. Therefore, developing low-cost, cobalt-free or low-cobalt high-capacity, high-energy-density structural energy storage composite electrode materials is both essential and extremely challenging. In view of this, this invention provides a high-capacity, high-entropy fluorine oxide material, its preparation method, and its applications. Summary of the Invention
[0004] The technical problem to be solved by this invention is to provide a high-capacity, high-entropy fluorine oxide material, its preparation method, and its applications. The aim is to address the problems of insufficient capacity, structural instability, and low energy storage density in cobalt-containing materials.
[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:
[0006] In a first aspect, a method for preparing a high-capacity, high-entropy fluorine oxide material includes the following steps:
[0007] Nickel source, M source, iron source, manganese source and magnesium source are dissolved in an alcohol solvent, and then a fluorine substitute and lithium carbonate are added to form a slurry; the M source is at least one of cobalt oxide, copper oxide and chromium trioxide; the slurry is ball-milled for the first time and then dried to obtain a fluorine oxide material precursor;
[0008] The fluorine oxide material precursor is calcined under an inert atmosphere (e.g., Ar), and then naturally cooled before being ball-milled a second time to obtain the fluorine oxide material.
[0009] Based on the above technical solution, the present invention can be further improved as follows.
[0010] Furthermore, the nickel source includes nickel oxide; the iron source includes ferric oxide; the manganese source includes manganese monoxide; the magnesium source includes magnesium oxide; the alcohol solvent includes ethanol; and the fluorine substitute includes lithium fluoride. The amount of alcohol added is adjusted as needed.
[0011] Furthermore, the molar ratio of nickel ions in the nickel source, M ions in the M source, iron ions in the iron source, manganese ions in the manganese source, and magnesium ions in the magnesium source is 1-2:1-2:1-2:1-2:1-2;
[0012] The ratio of the fluorine substitute to the total mass of the nickel source, the M source, the iron source, the manganese source, and the magnesium source is 1:0.5 to 1; the lithium carbonate accounts for 8% to 10% of the total mass of the nickel source, the M source, the iron source, the manganese source, and the magnesium source;
[0013] The parameters for the first ball milling are: 300-400 rpm / min, and the time is 8-12 hours;
[0014] The drying parameters are: temperature 60-80℃, time 12-24h; vacuum drying is used.
[0015] The calcination parameters are: heating rate of 3-8℃ / min, temperature of 800-900℃, and processing time of 2-5h; for example, placing it in a porcelain boat and transferring it to a tube furnace for calcination;
[0016] The parameters for the second ball milling are: 300-500 rpm / min, and the time is 5-8 hours.
[0017] Secondly, a high-capacity, high-entropy fluorine oxide material, said fluorine oxide material being prepared by the aforementioned preparation method.
[0018] Thirdly, the application of a high-capacity, high-entropy fluorinated oxychloride material, which is used in the preparation of structural energy storage composite material devices.
[0019] Furthermore, the device for preparing structural energy storage composite materials includes either a structural lithium-ion battery or a structural capacitor.
[0020] Fourthly, a positive electrode comprising the aforementioned high-capacity, high-entropy fluorine oxide material.
[0021] Fifthly, a method for preparing a positive electrode includes the following steps:
[0022] An electrode slurry is obtained by adding an active material, a binder, and a conductive agent to a solvent. The active material is a high-capacity, high-entropy fluorinated compound material. The electrode slurry is then coated onto carbon fibers and dried to obtain a positive electrode. The solvent can be N-methylpyrrolidone, etc.
[0023] Furthermore, the mass ratio of the active material, the binder, and the conductive agent is 6-8:1-2:1-2; the total mass ratio of the active material, the binder, and the conductive agent to the N-methylpyrrolidone solvent is 2-3:1.
[0024] The electrode paste is coated on the carbon fiber with a thickness of 40–60 μm.
[0025] The binder may be polyvinylidene fluoride (PVDF); the conductive agent may be conductive carbon black (Super P).
[0026] Sixthly, a structural lithium-ion battery, the structural lithium-ion battery including the aforementioned positive electrode. The structural lithium-ion battery is a layered porous structure material.
[0027] The method for preparing the battery cell of the lithium-ion battery structure includes the following steps:
[0028] Epoxy resin and pore-forming agent are stirred thoroughly at a mass ratio of 1:2-4 for 20-40 minutes. Then, curing agent (resin to curing agent mass ratio of 100:57.5) is added and stirred again for 20-30 minutes. The mixture is filtered to remove air bubbles, and then introduced into a vacuum bag by vacuum infusion. Two-step curing is performed: first, the temperature is raised to 130℃ for 60 minutes, and then raised to 180℃ and held for 30 minutes, with a heating rate of 5℃ / min. The mixture is then allowed to cool naturally to room temperature. The cured material is then removed and soaked in water for 24-48 hours (with water changed every 3-5 hours). Finally, lithium-ion secondary electrolyte (LB-266) is injected, and the mixture is assembled with the positive and negative electrodes, sealed, and left to stand for 24-36 hours to obtain the battery cell. Electrochemical tests are then performed.
[0029] The epoxy resin can be 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (TETRAD-C), the pore-forming agent can be polyethylene glycol 200 (PEG200), and the curing agent can be 4,4'-diaminodicyclohexylmethane.
[0030] The present invention has the following beneficial effects:
[0031] (1) This invention uses nickel source, M source, iron source, manganese source and magnesium source as raw materials, and combines them with fluorine substitutes. Through chemical and physical mixing and high-temperature pyrolysis, different kinds of metal oxide salts and fluorine substitutes are used to prepare layered fluorine oxides with small particle size, stable structure and high capacity and high entropy.
[0032] (2) The reaction system of this invention contains a fluorine substitute, which replaces part of the oxygen to stabilize the crystal structure, improve the battery cycle performance, and achieve structural stability during charge and discharge. Therefore, by optimizing the substitute and process parameters, a layered structure with sufficient interfacial bonding and stable structure is achieved. This is beneficial to the structural stability during charge and discharge, the formation of the interfacial film at the interface, and the re-intercalation of lithium ions, thereby improving capacity and cycle stability.
[0033] (3) The process of this invention is simple, the cycle is short, and it is easy to control. The synthesis temperature is low, the cost is low, and it is easy to promote and use.
[0034] (4) The present invention applies the prepared fluorine oxide material to the electrode material of structured lithium ions. The electrode material can achieve cycle stability, high capacity and good energy storage density, which meets the requirements of the electrode material of structured lithium ions.
[0035] (5) This invention coats high-capacity, high-entropy fluoride compound electrode active material onto carbon fiber to form a positive electrode of lithium-ion structural energy storage composite material with sufficient interfacial bonding, small interlayer thickness in the structural battery, stable structure, and high capacity. This not only expands the types of positive electrode active materials for structural lithium-ion and develops a new variety of positive electrode materials with excellent performance, but also enables controllable fluorine substitution, sufficient interfacial bonding, and stable structure, effectively overcoming the problems of insufficient capacity, unstable structure, and low energy storage density of existing cobalt-containing materials. Attached Figure Description
[0036] Figure 1 This is a scanning electron microscope image of the high-capacity, high-entropy fluoride oxycarbon material prepared according to Example 1 of the present invention;
[0037] Figure 2 These are charge-discharge capacity diagrams of the high-capacity high-entropy fluoride compound materials and high-entropy oxide electrode materials prepared according to Embodiments 1, 2, 3 and 4 of the present invention.
[0038] Figure 3 These are capacity retention curves of the high-capacity, high-entropy fluoride compound material prepared in Example 1 and the high-capacity, high-entropy oxide compound material prepared in Example 2 of this invention. Detailed Implementation
[0039] The principles and features of this invention are described below. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they should be performed according to the techniques or conditions described in the literature in this field, or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.
[0040] Example 1:
[0041] This embodiment relates to a method for preparing a structural lithium-ion battery, the steps of which are as follows:
[0042] (1) Preparation of high-entropy fluoride active materials
[0043] Equivalent amounts of nickel oxide, cobalt oxide, ferric oxide, manganese monoxide, and magnesium oxide were dissolved in 10 mL of ethanol. LiF was added in a 1:1 mass ratio (the mass ratio of nickel oxide, cobalt oxide, ferric oxide, manganese monoxide, and magnesium oxide to LiF), and lithium carbonate was added at 8% of the total mass of nickel oxide, cobalt oxide, ferric oxide, manganese monoxide, and magnesium oxide. The slurry was then ball-milled for the first time at 350 rpm for 10 hours (ethanol will evaporate during this process, so sealing is necessary). The mixture was then vacuum-dried overnight at 70°C to obtain a fluorinated oxide material precursor. This precursor was placed in a ceramic boat and transferred to a tube furnace. Under an Ar atmosphere, it was heat-treated at 900°C for 2 hours at a heating rate of 5°C / min. After natural cooling, it was ball-milled a second time at 500 rpm for 8 hours to obtain a high-capacity, high-entropy fluorinated oxide material.
[0044] (2) Fabrication of positive / negative electrode structure
[0045] The positive and negative electrode active materials, binder (PVDF), and conductive agent (carbon black) were added sequentially to N-methylpyrrolidone solvent in a mass ratio of 8:1:1, wherein the weight ratio of solvent to the sum of binder (PVDF), conductive agent (carbon black), and active materials was 2.6:1. The positive electrode active material was a high-capacity, high-entropy fluorinated compound material prepared in this invention, and the negative electrode active material was an energy-type graphite material. Next, the stirred slurry was coated onto carbon fiber at a thickness of 40 μm using a blade coating method and dried at 90°C until all solvent evaporated. Finally, it was cut to the required size to obtain the positive and negative electrodes.
[0046] (3) Fabrication of structural lithium-ion batteries (i.e., lithium-ion structural energy storage composite structure batteries)
[0047] The tetrafunctional epoxy resin and pore-forming agent PEG200 were stirred thoroughly for 20 minutes at a mass ratio of 1:3. Then, the curing agent PACM (resin to curing agent mass ratio of 100:57.5) was added and stirred again for 20 minutes. The mixture was filtered to remove air bubbles, and then introduced into a vacuum bag via vacuum infusion. Two-step curing was performed: first, the temperature was raised to 130℃ for 60 minutes, then raised to 180℃ and held for 30 minutes, with a heating rate of 5℃ / min for both steps, followed by natural cooling to room temperature. The cured battery cell was removed and soaked in water for 24 hours (water changed every 5 hours). Finally, lithium-ion secondary electrolyte (LB-266) was injected, and the battery was assembled with the positive and negative electrodes, sealed, and allowed to stand for 24 hours for electrochemical testing. The battery's discharge capacity at a current density of 10 mA / g was 259.48 mAh / g, with a coulombic efficiency greater than 99%, and the capacity retention was 59.34% after 275 cycles. (Table 1) Figure 1 , Figure 2 , Figure 3 ).
[0048] Example 2: Comparative Example
[0049] This embodiment relates to a method for preparing a structural lithium-ion battery, the steps of which are as follows:
[0050] (1) Preparation of high-entropy oxide active materials
[0051] Equivalent amounts of nickel oxide, cobalt oxide, ferric oxide, manganese monoxide, and magnesium oxide were dissolved in 10 mL of ethanol. 8% lithium carbonate was added, calculated as the sum of the masses of nickel oxide, cobalt oxide, ferric oxide, manganese monoxide, and magnesium oxide. The slurry was then ball-milled for the first time at 350 rpm for 10 hours (ethanol will evaporate during this process, so sealing is necessary). The resulting slurry was vacuum-dried overnight at 70°C to obtain an oxide material precursor. This oxide material precursor was placed in a ceramic boat and transferred to a tube furnace. Under an Ar atmosphere, it was heat-treated at 900°C for 2 hours at a heating rate of 5°C / min. After natural cooling, it was then ball-milled at 500 rpm for 8 hours to obtain the oxide material.
[0052] (2) Fabrication of positive / negative electrode structure
[0053] Positive and negative electrode active materials, binder (PVDF), and conductive agent (carbon black) were added sequentially in an N-methylpyrrolidone solvent at a mass ratio of 8:1:1, with a solvent-to-material weight ratio of 2.6:1. The positive electrode active material was an oxide material, and the negative electrode active material was an energy-type graphite material. The stirred slurry was then coated onto carbon fibers to a thickness of 40 μm using a blade coating method and dried at 90°C until all the solvent evaporated. Finally, the electrodes were cut to the required size to obtain the positive and negative electrodes.
[0054] (3) Fabrication of lithium-ion structure energy storage composite battery
[0055] The tetrafunctional epoxy resin and pore-forming agent PEG200 were stirred thoroughly for 20 minutes at a mass ratio of 1:3. Then, the curing agent PACM (resin to curing agent mass ratio of 100:57.5) was added and stirred again for 20 minutes. The mixture was filtered to remove air bubbles, and then introduced into a vacuum bag via vacuum infusion. Two-step curing was performed: first, the temperature was raised to 130℃ for 60 minutes, then raised to 180℃ and held for 30 minutes, with a heating rate of 5℃ / min for both steps, followed by natural cooling to room temperature. The cured battery cell was removed and soaked in water for 24 hours (water changed every 5 hours). Finally, lithium-ion secondary electrolyte (LB-266) was injected, and the battery was assembled with the positive and negative electrodes, sealed, and allowed to stand for 24 hours for electrochemical testing. The battery's discharge capacity at a current density of 10 mA / g was 183.52 mAh / g, with a coulombic efficiency greater than 98%, and the capacity retention after 275 cycles was 45.06%. (Table 1) Figure 2 , Figure 3 ).
[0056] Example 3:
[0057] This embodiment relates to a method for preparing a structural lithium-ion battery, the steps of which are as follows:
[0058] (1) Preparation of cobalt-free high-entropy fluoride active materials
[0059] If the cobalt oxide in Example 1 is replaced with copper oxide or chromium trioxide, the other steps are as follows:
[0060] Equivalent amounts of nickel oxide, copper oxide, manganese monoxide, and magnesium oxide were dissolved in 10 mL of ethanol. LiF in a 1:1 mass ratio (sum of the masses of nickel oxide, copper oxide, ferric oxide, manganese monoxide, and magnesium oxide) and 8% lithium carbonate were added. The slurry was ball-milled for the first time at 350 rpm for 10 hours (ethanol will evaporate during this process, so sealing is necessary). The mixture was then vacuum-dried overnight at 70°C to obtain a fluorinated oxide material precursor. This precursor was placed in a ceramic boat and transferred to a tube furnace. Under an Ar atmosphere, it was heat-treated at 900°C for 2 hours at a heating rate of 5°C / min. After natural cooling, it was ball-milled a second time at 500 rpm for 8 hours to obtain a high-capacity, high-entropy fluorinated oxide material.
[0061] (2) Fabrication of positive / negative electrode structure
[0062] Positive and negative electrode active materials, binder (PVDF), and conductive agent (carbon black) were added sequentially to N-methylpyrrolidone solvent in a mass ratio of 8:1:1, wherein the weight ratio of solvent to the sum of binder (PVDF), conductive agent (carbon black), and active materials was 2.6:1. The positive electrode active material was a high-capacity, high-entropy fluorinated compound material, and the negative electrode active material was a lithium metal sheet composite material. The stirred slurry was then coated onto carbon fiber at a thickness of 40 μm using a blade coating method and dried at 90°C until all solvent evaporated. Finally, it was cut to the required size to obtain the positive and negative electrodes.
[0063] (3) Fabrication of structural lithium-ion batteries (i.e., lithium-ion structural energy storage composite structure batteries)
[0064] The tetrafunctional epoxy resin and pore-forming agent PEG200 were stirred thoroughly for 20 min at a mass ratio of 1:3. Then, the curing agent PACM (resin to curing agent mass ratio of 100:57.5) was added and stirred again for 20 min. The mixture was filtered to remove air bubbles, and then introduced into a vacuum bag via vacuum infusion. Two-step curing was performed: first, the temperature was raised to 130℃ for 60 min, then raised to 180℃ and held for 30 min, with a heating rate of 5℃ / min for both steps, followed by natural cooling to room temperature. The cured battery cell was removed and soaked in water for 24 h (water changed every 5 h). Finally, lithium-ion secondary electrolyte (LB-266) was injected, and the battery was assembled with the positive and negative electrodes, sealed, and allowed to stand for 24 h for electrochemical testing. The battery's discharge capacity at a current density of 10 mA / g was 196.61 mAh / g (Table 1 and...). Figure 2 ).
[0065] Example 4:
[0066] Compared to Example 3, copper oxide was replaced with chromium trioxide, otherwise the same as in Example 3. The battery's discharge capacity at a current density of 10 mA / g was 234.47 mAh / g (Table 1 and...). Figure 2 ).
[0067] Table 1. Discharge specific capacity of embodiments one to four of the present invention.
[0068]
[0069] In summary, the fluorine substitute in the reaction system of this invention partially replaces oxygen, thereby stabilizing the crystal structure, improving battery cycle performance, and achieving structural stability during charge and discharge. Therefore, by optimizing the substitute and process parameters, a layered structure with sufficient interfacial bonding and structural stability is achieved. This is beneficial for structural stability during charge and discharge, the formation of interfacial films at the interfaces, and the re-intercalation of lithium ions, thus improving capacity and cycle stability.
[0070] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a high-capacity, high-entropy fluorine oxide material, characterized in that, Includes the following steps: Nickel source, M source, iron source, manganese source and magnesium source are dissolved in an alcohol solvent, and then a fluorine substitute and lithium carbonate are added to form a slurry; the M source is at least one of cobalt oxide, copper oxide and chromium trioxide; the slurry is ball-milled for the first time and then dried to obtain a fluorine oxide material precursor; The fluorine oxide material precursor was calcined under an inert atmosphere, and after natural cooling, it was ball-milled a second time to obtain the fluorine oxide material. The nickel source includes nickel oxide; the iron source includes ferric oxide; the manganese source includes manganese monoxide; the magnesium source includes magnesium oxide; the alcohol solvent includes ethanol; and the fluorine substitute includes lithium fluoride. The molar ratio of nickel ions in the nickel source, M ions in the M source, iron ions in the iron source, manganese ions in the manganese source, and magnesium ions in the magnesium source is 1~2:1~2:1~2:1~2:1~2; The ratio of the fluorine substitute to the total mass of the nickel source, the M source, the iron source, the manganese source, and the magnesium source is 1:0.5~1; the lithium carbonate accounts for 8%~10% of the total mass of the nickel source, the M source, the iron source, the manganese source, and the magnesium source; The parameters for the first ball milling are: 300~400 rpm, and the time is 8~12 h; The drying parameters are: temperature 60~80℃, time 12~24 h; The calcination parameters are: heating rate of 3~8℃ / min, temperature of 800~900℃, and treatment time of 2~5 h; The parameters for the second ball milling are: 300~500 rpm, and the time is 5~8 h.
2. A high-capacity, high-entropy fluorine oxide material, characterized in that, The fluorine oxide material is prepared by the preparation method described in claim 1.
3. An application of a high-capacity, high-entropy fluorine oxide material, characterized in that, The high-capacity, high-entropy fluorine oxide material described in claim 2 is used in the preparation of structural energy storage composite material devices.
4. The application of the high-capacity, high-entropy fluorine oxide material according to claim 3, characterized in that, The device for preparing structural energy storage composite materials includes either a structural lithium-ion battery or a structural capacitor.
5. A positive electrode, characterized in that, The positive electrode comprises a high-capacity, high-entropy fluorine oxide material as described in claim 2.
6. The method for preparing a positive electrode according to claim 5, characterized in that, Includes the following steps: An active material, a binder, and a conductive agent are added to a solvent to obtain an electrode slurry. The active material is a high-capacity, high-entropy fluorinated compound material as described in claim 2. The electrode slurry is coated onto carbon fiber and dried to obtain a positive electrode.
7. The method for preparing a positive electrode according to claim 6, characterized in that, The mass ratio of the active material, the binder, and the conductive agent is 6~8:1~2:1~2; the total mass ratio of the active material, the binder, and the conductive agent to the solvent is 2~3:
1. The electrode paste is coated on the carbon fiber with a thickness of 40~60 μm.
8. A structural lithium-ion battery, characterized in that, The lithium-ion battery structure includes a positive electrode as described in claim 5.
Citation Information
Patent Citations
Lithium-doped high-entropy oxide battery negative electrode material as well as preparation and application methods thereof
CN112537804A
High-entropy positive electrode material and preparation method and application thereof
CN115394985A
Carbon fiber electrode with current collector and tab integrally formed and preparation method and application of carbon fiber electrode
CN118825200A